2000
DOI: 10.1080/14628830050516470
|View full text |Cite
|
Sign up to set email alerts
|

Hair reduction using a new intense pulsed light irradiator and a normal mode ruby laser

Abstract: The IPL was found to be 3.94 times more effective than the ruby laser for hair removal. In the chin and neck region, more than 3 treatments with the IPL did not improve the therapeutic result significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…Intense pulsed light-based systems 12 and such lasers as the longpulsed Nd:YAG, long-pulsed diode, alexandrite, and the Q-switched Nd:YAG, have been shown to be beneficial in hair reduction. 11,[13][14][15] Lasers and IPLs are associated with infrequent complications; the greatest risk being associated with the treatment of darker skin types. 16,17 These adverse effects, which include hyperpigmentation, hypopigmentation, blistering, and crusting, are often associated with the treatment of skin types IV and above.…”
Section: Discussionmentioning
confidence: 99%
“…Intense pulsed light-based systems 12 and such lasers as the longpulsed Nd:YAG, long-pulsed diode, alexandrite, and the Q-switched Nd:YAG, have been shown to be beneficial in hair reduction. 11,[13][14][15] Lasers and IPLs are associated with infrequent complications; the greatest risk being associated with the treatment of darker skin types. 16,17 These adverse effects, which include hyperpigmentation, hypopigmentation, blistering, and crusting, are often associated with the treatment of skin types IV and above.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Schröter et al and Sadick et al postulate that damage to the hair follicle and hair shaft in the anagen phase cause a long-term interruption in the hair growth cycle [48][49][50]. A number of workgroups have demonstrated good results using IPL systems [12,[51][52][53][54][55][56].…”
Section: Hair Removalmentioning
confidence: 99%
“…The reported types of immediate damage include severe damage to the hair shafts, the follicle inner root sheath (IRS) and outer root sheath (ORS), including thermal coagulation and vaporization injury [8][9][10][11][12][13]. It has also been shown that effective hair reduction can be obtained even though the hair shaft remains in place for several days before being shed [14]. It is hypothesized that permanent HF damage is obtained if the stem cells of the follicle in the ''bulge'' area are damaged, disabling the processes of hair follicle re-growth [1,2,15,16].…”
Section: Introductionmentioning
confidence: 99%